2013
DOI: 10.1177/0021998313514258
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic properties of syntactic foam reinforced with short sisal fibers

Abstract: Application of natural fibers has attracted a great deal of attention among the composite research community in the past couple of decades. In this study, sisal fiber was utilized in fabrication of syntactic foam to improve the mechanical properties. Four sets of samples with different volume fractions of sisal fibers (0%, 1.5%, 2.5%, and 3.5%) were prepared. Viscoelastic properties of the samples were characterized with dynamic mechanical analysis. Storage and loss moduli, complex viscosity, and damping facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…[1][2][3] The significances of using natural fiber reinforced polymer composites are multifold, with few being, environmental friendly, less health problem, low cost, and comparative thermal and mechanical properties when compared with synthetic fiber reinforced composites. Many natural fibers such as sisal, 4 kenaf, 5 coir, 6 and jute 7 fibers have proven valuable alternative to synthetic fibers. Over the past 10 years, the development of banana fiber reinforced composites has also attracted significant research interest.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The significances of using natural fiber reinforced polymer composites are multifold, with few being, environmental friendly, less health problem, low cost, and comparative thermal and mechanical properties when compared with synthetic fiber reinforced composites. Many natural fibers such as sisal, 4 kenaf, 5 coir, 6 and jute 7 fibers have proven valuable alternative to synthetic fibers. Over the past 10 years, the development of banana fiber reinforced composites has also attracted significant research interest.…”
Section: Introductionmentioning
confidence: 99%
“…The improved E' values compared to NE at 50°C and 60°C can be attributed to good interaction and interfacial bonding between the HGM and NE molecules during mixing resulting in imcreased flexural strength of SFC mostly at lower volume fraction and higher particle sizes [30], [53]. Figure 10 (a-d) shows the loss modulus (E'') of the SFCs which is the viscous response and a measure of the energy dissipated at heat per cycle under the deformation of the composites.…”
Section: Dynamic Mechanical Analysismentioning
confidence: 99%
“…Dynamic mechanical analysis is one of the most appropriate method to investigate relaxation events. 36 It has been demonstrated that the interpretation of viscoelastic relaxation strength in polymers depends on the tangent of the phase angle (tand) or real (in-phase) or imaginary (out-of-phase) components of storage and loss modulus, respectively. 37 The glass transition temperature of a material, also referred as a-transition, is normally considered as the temperature-dependent peak of tand (Figure 6).…”
Section: Effect Of Fillers On Apparent Activation Energy For Viscoelastic Relaxationmentioning
confidence: 99%